Detailed analysis of an enriched deep intronic ABCA4 variant in Irish Stargardt disease patients - Farrar, Gwyneth (My University, 2023)
Over 15% of probands in a large cohort of more than 1500 inherited retinal degeneration patients present with a clinical diagnosis of Stargardt disease (STGD1), a recessive form of macular dystrophy caused by biallelic variants in the ABCA4 gene. Participants were clinically examined and underwent either target capture sequencing of the exons and some pathogenic intronic regions of ABCA4, sequencing of the entire ABCA4 gene or whole genome sequencing. ABCA4 c.4539 + 2028C > T, p.[= ,Arg1514Leufs*36] is a pathogenic deep intronic variant that results in a retina-specific 345-nucleotide pseudoexon inclusion. Through analysis of the Irish STGD1 cohort, 25 individuals across 18 pedigrees harbour ABCA4 c.4539 + 2028C > T and another pathogenic variant. This includes, to the best of our knowledge, the only two homozygous patients identified to date. This provides important evidence of variant pathogenicity for this deep intronic variant, highlighting the value of homozygotes for variant interpretation. 15 other heterozygous incidents of this variant in patients have been reported globally, indicating significant enrichment in the Irish population. We provide detailed genetic and clinical characterization of these patients, illustrating that ABCA4 c.4539 + 2028C > T is a variant of mild to intermediate severity.
PUBLISHED
Keywords: irish population; ABCA4 gene; retinal degeneration; irish population; ABCA4 gene; retinal degeneration